1990
DOI: 10.2302/kjm.39.187
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of nonanginal chest pain.

Abstract: The term "atypical chest pain" is a wastebasket term that leads physicians to send any patient with chest pain to coronary angiography. In order to avoid this term, we must learn to distinguish atypical angina from nonanginal chest pain before angiography is considered in order to avoid unnecessary invasive procedures. A chest pain is very likely nonanginal if its duration is over 30 minutes or less than 5 seconds, it increases with inspiration, can be brought on with one movement of the trunk or arm, can be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
16
0
6
Order By: Relevance
“…In a meta‐analysis by Chun and McGee and Panju et al, chest‐pain characteristics such as pressure and the like were not enough to be independently useful in establishing a MI diagnosis. Classic duration of pain lasting >30 minutes can be indicative of either an AMI or a nonischemic etiology, like gastroesophageal disease . In a meta‐analysis of 64 studies, chest‐pain duration >30 minutes suggested low likelihood of MI (LR+: 0.1) .…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis by Chun and McGee and Panju et al, chest‐pain characteristics such as pressure and the like were not enough to be independently useful in establishing a MI diagnosis. Classic duration of pain lasting >30 minutes can be indicative of either an AMI or a nonischemic etiology, like gastroesophageal disease . In a meta‐analysis of 64 studies, chest‐pain duration >30 minutes suggested low likelihood of MI (LR+: 0.1) .…”
Section: Discussionmentioning
confidence: 99%
“…Expect in the case of obvious nerve root compression, neurologic findings are often absent or nonfocal 16 . A positive spurling maneuver have specificity of 94.0% with cervical nerve root pathology 17 .…”
Section: Discussionmentioning
confidence: 98%
“…Em nosso caso, a paciente apresentava dor na região cervical irradiada para MSE, déficit de força muscular e diminuição do reflexo bicipital, o que se encontra de acordo com vários autores. 1,4,10,15,16 O tratamento da AC é cirúrgico. A descompressão cirúrgica pode ser feita por via anterior ou posterior.…”
Section: Discussionunclassified